Gut microbiome and metabolome to discover pathogenic bacteria and probiotics in ankylosing spondylitis - Lai, Yupeng; Tang, Wenli; Luo, Xiao; Zheng, Huihui; Zhang, Yanpeng; Wang, Meiying; Yu, Guangchuang; Yang, Min (Frontiers in Immunology, 2024)
Previous research partially reveals distinct gut microbiota in ankylosing spondylitis (AS). In this study, we aim to perform non-targeted fecal metabolomics in AS and to discover the microbiome-metabolome interface in AS. Based on prospective cohort studies, we further explore the impact of tumor necrosis factor inhibitor (TNFi) on gut microbiota and metabolites in AS.To further understand gut microbiota and metabolites in AS, along with TNFi's influence, we initiated a prospective cohort study. Fecal samples were collected from 29 AS patients before and after TNFi therapy, and 31 healthy controls. Metagenomic and metabolomic experiments were performed with fecal samples, and validating experiments were performed based on association between microbiota and metabolites.By using the metagenomic sequencing system and profiling microbial community taxonomic composition, we annotate 7703 species, and by using metabolites profiling, we identified 50046 metabolites. Different microbials and metabolites were discovered between AS patients and health controls. Moreover, TNFi was confirmed to partially restore the gut microbiota and metabolites. Through multi-omics analysis of microbiota and metabolites, we also discovered associations between differential microbes and metabolites, identifying compounds like oxypurinol and biotin that are correlated with inhibiting pathogenic bacteria Ruminococcus gnavus and promoting probiotic bacteria Bacteroides uniformis. Through experimental studies, we further confirmed the relationship between microbes and metabolites and explored the impact of these two types of microbes on enterocytes and inflammatory cytokine IL-18.In summary, our multi-omic exploration illuminates TNFi's impact on gut microbiota and metabolites and proposes a novel therapeutic perspective: by supplementing compounds to inhibit potential pathogenic bacteria and promote potential probiotics, to control inflammation in AS.